A male giant violating the Earth: communal spirit, sexual dissidence, and regional colour in twentieth-century Canadian prairie fiction = Un gigante violando a la tierra: espíritu comunal, disidencia sexual y color regional en la ficción - Carmona Rodríguez, Pedro (Estudios Ingleses de la Universidad Complutense, 2004)
When it is still a matter of debate, the gendered and sexual dimension of the national discourse is currently fostering attention onto the gendered constituent of other modern collectives like region or locality. In the light of the opening of the national entity to these features, this paper explores the collective constitution in the regional sphere through a sample of twentieth-century Canadian prairie fiction. This scope uncovers as a territory of gender and sexual ambivalence where the symbolic communal narrative is confronted with the semiotic traces deriving from the individual’s attachment to the (mother-) land. For the sake of its own renewal, the communal self puts in practice an abiding mechanism of self-regeneration that lays bare the dynamics of reproduction of the same and homogenisation of the different, while it endlessly displaces an other erected in terms of sexuality and dissidence from the communal heteronorm.